Socioeconomics of Agriculture - Mann, Stefan (SpringerBriefs in Economics, 2018)
This open access book applies for the first time emerging concepts of socioeconomics to analyse an economic sector, namely agriculture. It considers the rational choices of all actors in the system (just as agricultural economists do) and their cultural preferences and constraints (just as rural sociologists do). Socioeconomic concepts are subsequently used to structure agricultural issues with regard to the three governance mechanisms (hierarchy, markets, and cooperation), and different agricultural systems are presented and compared. The book will be of interest to social scientists with various backgrounds, and seeks to break down the barriers of single-disciplinary thinking.